Tors in Central European Mountains – are they indicators of past environments? - Michniewicz, Aleksandra (Bulletin of Geography. Physical Geography Series, 2019)
Tors represent one of the most characteristic landforms in the uplands and mountains of Central Europe, including the Sudetes, Czech-Moravian Highlands, Šumava/Bayerischer Wald, Fichtelgebirge or Harz. These features occur in a range of lithologies, although granites and gneisses are particularly prone to tor formation. Various models of tor formation and development have been presented, and for each model the tors were thought to have evolved under specific environmental conditions. The two most common theories emphasised their progressive emergence from pre-Quaternary weathering mantles in a two-stage scenario, and their development across slopes under periglacial conditions in a one-stage scenario. More recently, tors have been analysed in relation to ice sheet extent, the selectivity of glacial erosion, and the preservation of landforms under ice. In this paper we describe tor distribution across Central Europe along with hypotheses relating to their formation and development, arguing that specific evolutionary histories are not supported by unequivocal evidence and that the scenarios presented were invariably model-driven. Several examples from the Sudetes are presented to demonstrate that tor morphology is strongly controlled by lithology and structure. The juxtaposition of tors of different types is not necessarily evidence that they differ in their mode of origin or age. Pathways of tor remodelling and degradation under subaerial conditions are identified and it is argued that processes of tor formation and development are ongoing. Thus, tors are not reliable indicators of past environments, because they are considerably influenced by both geological factors, such as lithology and structure, and geomorphological factors such as hillslope setting.